Modified Genetic Algorithm To Determine The Location Of The Distribution Power Supply Networks In The City - Fedorchenko, Ievgen; Andrii, Oliinyk; Jamil Alsayaydeh, Jamil Abedalrahim; Kharchenko, Anastasia; Stepanenko, Aleksandr; Shkarupylo, Vadym (Asian Research Publishing Network (ARPN), 2020)
The problem of combinatorial optimization in relation to the choice of location of power supplies in solving the problem of development of urban power distribution networks is considered. Two methods of placing power supplies and securing consumers for them have been developed to solve this problem. The first developed method is to place power supplies of the same size, and the second - different sizes. The fundamental difference between the created methods and the existing ones is that the proposed methods take into account all the material of the task and have specialized ways to encode possible solutions, modified crossbreeding and selection operators. Proposed methods effectively address the problem of low inheritance, topological impracticability of the found solutions, as a result of which the execution time was significantly reduced and the accuracy of calculations increased. In the developed methods the absence of the account of restrictions on placement of new power supplies which has allowed to solve a problem of application of methods for a narrow range of tasks is realized. A comparative analysis of the results obtained by placing power supplies of the same size and known methods was performed, and it was found that the developed method works faster than known methods. It is shown that the proposed approach provides a stable convergence of the search process for an acceptable number of steps without artificially limiting the search space and the use of additional expert information on the feasibility of possible solutions. The obtained results allow to offer effective methods for improving the quality of decisions made on the choice of location of power supply facilities in the design of urban electricity